COMPARATIVE STUDY OF LINEAR AND NON-LINEAR THEORIES ONE-DIMENSIONAL CONSOLIDATION OF THICK CLAY LAYERS - P. Ayub Khan; M. R. Madhav; E. S. Reddy (International Association of Lowland Technology, 2012)
The classical theory of consolidation developed by Terzaghi is based on linear void ratio-effective stress relationship, thin layer of clay with negligible self weight, infinitesimal strain, constant volume (1+void ratio) and constant coefficients of permeability, volume compressibility and consolidation. This paper presents a simplified theory of non-linear one-dimensional consolidation of a thick clay deposit considering linear void ratio-log effective stress relationship, self weight of soil, constant volume (1+void ratio), thickness of clay layer and coefficient of consolidation but neglecting the slight variation of initial void ratio with depth. The proposed equation for consolidation of the deposit is solved numerically by the finite difference method and the results compared with those of the conventional linear theory. The results indicate that the variation of degree of settlement with time is relatively large while the variation of the degree of dissipation of excess pore pressure with time is relatively small in the case of thick layer of clay compared to those for thin layer. The variations of degrees of settlement and the dissipation of pore pressures are sensitive to the magnitude of applied load relative to the thickness of the deposit unlike in the conventional theory for thin layer. The isochrones in the case of pervious top and pervious bottom boundary conditions are slightly skewed in contrast to symmetrical isochrones of conventional linear theory.